2013
DOI: 10.1002/maco.201307118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a nickel alloy coating on the corrosion of furnace wall tubes in a waste wood fired power plant

Abstract: The use of waste wood as a fuel in power plants is becoming more widespread in Europe, because it is a renewable energy source with a lower cost than forest fuel. However it is more corrosive than coal and corrosion problems have arisen in the furnace wall area of a low NOx heat and power boiler. The furnace walls are made of a low alloy steel which has been coated in some parts with a nickel alloy to reduce corrosion. In this work, furnace tubes coated with a nickel alloy were compared to the uncoated tubes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The reference material used was a 16Mo3 sample ring, overwelded with Inconel 625. This has been exposed various times in similar field exposures (biomass‐ and waste‐fired boilers) due to its exceptionally high corrosion resistance and can therefore be used as a measure of the corrosivity of the present conditions. A disadvantage with the overweld is that the sample ring thickness is not even and accurate thickness measurements for calculation of material loss was therefore not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The reference material used was a 16Mo3 sample ring, overwelded with Inconel 625. This has been exposed various times in similar field exposures (biomass‐ and waste‐fired boilers) due to its exceptionally high corrosion resistance and can therefore be used as a measure of the corrosivity of the present conditions. A disadvantage with the overweld is that the sample ring thickness is not even and accurate thickness measurements for calculation of material loss was therefore not possible.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] One method to increase the steam oxidation resistance of the alloy structural components is to modify the composition to form a protective external Cr2O3-based scale. [9][10][11][12] It is well-known that increasing an alloy Cr-content can enhance the formation of a protective external Cr2O3-based scale.…”
Section: Introductionmentioning
confidence: 99%
“…Abels et al have shown, that at high temperatures Cl 2 acts more corrosive to metallic materials than HCl. However, both species are able to form volatile metal chlorides and oxychlorides with metal oxides or with metallic elements of the bulk alloy . The generation of metal chlorides requires the supply of the oxide/metal interface with chloride‐bearing educts.…”
Section: Discussionmentioning
confidence: 99%